Study on the effect of carboxymethyl cellulose (CMC) concentration on the quality of lacum fruit syrup (Cayratia trifolia (L.) Domin) - Priyono, Suko; Saputri, Nur Endah; Ramadan, Qhori (Jurnal Inovasi Pangan dan Gizi, 2025)
Background : Syrup made from lacum fruit is one of the efforts to diversify processed products. The use of lacum fruit as a processed product has great potential in society, because the vitamin C content in lacum fruit has properties and benefits for the human body. Method: This study used a Randomized Block Design (RAK) with one factor, namely variations in CMC concentration with 5 levels, consisting of CMC 0%, CMC 0.5%, CMC 1%, CMC 1.5% and CMC 2%. Findings: CMC administration had a very strong tendency towards the characteristics of total dissolved solids, pH, the L* values ​​obtained tended to increase but the a* (reddish) and b* (yellowish) values ​​tended to decrease. Conclusion: The best lacum fruit syrup is syrup with a CMC concentration of 1% which produces an average chemical test in the form of a Total Dissolved Solids test of 45.80o Brix, a pH test of 3.93, an L color of 12.58, a* 2.52 and b* 0.26. The best sensory test results were color 3.81 (like), aroma 3.42 (like), taste 3.77 (like) and viscosity 3.77 (like). Novelty/Originality of This Study:This study explores the effect of varying carboxymethyl cellulose (CMC) concentrations on the physicochemical and sensory qualities of lacum fruit syrup. It provides new insights into the optimization of CMC for enhancing the quality of local fruit-based beverages.